Valvular Heart Disease in Pregnancy - Hilary Shapiro; Laith Alshawabkeh (Methodist DeBakey Cardiovascular Journal, 2024)
Valvular heart disease is a common cause of peripartum cardiovascular morbidity and mortality. The hemodynamic changes of pregnancy and their impact on pre-existing valvular lesions are described in this paper. Tools for the calculation of maternal and fetal risk during pregnancy are also discussed. The pathophysiology and management of valvular lesions, both obstructive and regurgitant, are then described, followed by a discussion of mechanical and bioprosthetic valve complications during pregnancy.